The effect of inter-letter spacing on the N170 during visual word recognition: An event-related potentials experiment. - Civera, Teresa; Perea, Manuel; Leone-Fernandez, Barbara; Vergara-Martínez, Marta (Cognitive, Affective & Behavioral Neuroscience, 2024)
Previous behavioral studies have shown that inter-letter spacing affects visual word recognition and reading. While condensed spacing may hinder the early stages of letter encoding because of increased crowding effects, the impact of expanded inter-letter spacing is still unclear. To examine the electrophysiological signature of inter-letter spacing on visual word recognition, we presented words in three different inter-letter spacing conditions (default, condensed [−1.5 points] or expanded [+1.5 points]) in an event-related potentials go/no-go semantic categorization task. Our focus was on the N170, an event-related potentials component associated with the early encoding of orthographic information, which also is sensitive to crowding effects. Results revealed that the N170 amplitude reached the largest values for the condensed condition than for the default and expanded spacing conditions, which did not differ. While increased crowding impacted the early encoding of orthographic information, extra letter spacing (compared with default spacing) did not. This outcome is consistent with the Modified Receptive Field hypothesis, in which letter receptors adapt their size to cope with letter crowding. These findings reveal that reducing the space between letters more than the default spacing impairs the ability to process written words, whereas slightly expanding the space between letters does not provide any additional benefit.